Protecting Global Rangelands for Biodiversity, Livelihoods and Climate Resilience - Rangelands Stewardship Council (Rangelands Stewardship Council, 2025)
The Rangeland Stewardship Council (RSC) is a global multi-stakeholder initiative that brings together pastoralists, scientists, practitioners, and market actors to strengthen how rangelands are managed and recognised. We support coordination across research, policy, and value chains, and recognise the essential role of the communities who steward these landscapes. Through inclusive governance and evidence-based approaches, we help create the conditions for effective stewardship and long-term resilience across rangeland regions. This is a set of posters displayed at the launch of the International Year of Rangelands and Pastoralists exhibition at FAO Headquarters in Rome, December 2025.